Cost Price of Products in the System of Heat, Refrigeration and Electric Energy Production Combined at Thermal Power Plant; MATEC Web of Conferences; Vol. 72 : Heat and Mass Transfer in the System of Thermal Modes of Energy – Technical and Technological Equipment (HMTTSC-2016) - Tubolev A. A. Aleksandr Anatolievich (2016, 2016)
Title screen